2010
DOI: 10.1016/j.pec.2010.06.017
|View full text |Cite
|
Sign up to set email alerts
|

The effects of physicians’ affect-oriented communication style and raising expectations on analogue patients’ anxiety, affect and expectancies

Abstract: Physicians should take into account that communicating in warm, empathic way combined with raising positive expectations seems to lead to the most favorable effects on patients' state anxiety and outcome expectancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
72
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 36 publications
10
72
0
3
Order By: Relevance
“…12 It has also been shown to reduce patient anxiety and increase their sense of outcome expectancy, thus enhancing a positive placebo effect. 13 Furthermore, physicians who see themselves as empathetic are perceived by their patients as being empathetic. …”
Section: The Physician and Empathymentioning
confidence: 99%
“…12 It has also been shown to reduce patient anxiety and increase their sense of outcome expectancy, thus enhancing a positive placebo effect. 13 Furthermore, physicians who see themselves as empathetic are perceived by their patients as being empathetic. …”
Section: The Physician and Empathymentioning
confidence: 99%
“…Mercer et al 4 showed a positive relationship both between GP empathy and patient enablement at the consultation, and between patient enablement and changes in the main symptom and well-being evaluated 3 months after the consultation. Finally, Verheul et al 5 investigated the impact of a warm and empathic consultation compared to a cold and formal consultation on the certainty of the outcome. The greatest beneficial effects of empathic communication on stress reduction and expectancies were observed when it was combined with a positive expectations style.…”
mentioning
confidence: 99%
“…To gain a child or youth's trust and that of their parents requires good communication [304][305][306].…”
Section: The Mechanism and Effects Of Ivlt In Chronic Painmentioning
confidence: 99%